2016
DOI: 10.1515/pjct-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and kinetic studies of sorption of 2.4-dichlorophenol onto 2 mixtures: bamboo biochar plus calcium sulphate (BC) and hydroxyapatite plus bamboo biochar plus calcium sulphate (HBC), in a fluidized bed circulation column

Abstract: Sorption studies were carried out to investigate removal of 2.4-dichlorophenol (2.4-DCP) from aqueous solution in a fl uidized bed by two types of adsorbent mixtures: BC (Bamboo char plus Calcium sulphate), and HBC (Hydroxyapatite plus Bamboo char plus Calcium sulphate); both manufactured in ball shape. The main material bamboo char was characterized by FTIR, DTA and SEM. The adsorption experiments were conducted in a fl uidized bed circulation column. Adsorption, isotherms and kinetic studies were established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Clearly, when pH is higher than 6, the adsorption equilibrium decreases. A similar phenomenon has been previously reported for the sorption of phenol and chlorophenols on different agrowaste-based biochar materials such as pine fruit shell biochar (PFS) 32 , pinus massoniana biochar 75 , food waste-based biochar (FWC) 42 , H. fusiformis biochar (HFB) 76 , FA-coated biochars 77 , magnetic biochar 46 , bamboo biochar 78 , and paper sludge/wheat husk biochar 79 . Thus, the optimum solution pH of 6 was chosen for other adsorption experimental studies.…”
Section: Xps Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…Clearly, when pH is higher than 6, the adsorption equilibrium decreases. A similar phenomenon has been previously reported for the sorption of phenol and chlorophenols on different agrowaste-based biochar materials such as pine fruit shell biochar (PFS) 32 , pinus massoniana biochar 75 , food waste-based biochar (FWC) 42 , H. fusiformis biochar (HFB) 76 , FA-coated biochars 77 , magnetic biochar 46 , bamboo biochar 78 , and paper sludge/wheat husk biochar 79 . Thus, the optimum solution pH of 6 was chosen for other adsorption experimental studies.…”
Section: Xps Analysissupporting
confidence: 82%
“…By the PSO, the (q e,cal ) values exhibit a good fit with the (q t,exp ) values owing to the low Chi-square (χ 2 ) and Δq t (%) values, which were in the range of 0.11-4.88 and 1.48-6.60% for the PSO kinetic model. Therefore, the results of this study show that the PSO model produces a superior fit for phenol and CPhs adsorption onto WAS-BC, which have similar trends; in addition, it is demonstrated that the kinetics of phenol, 4-CPh, and 2,4-DCPh sorption onto other sorbents also followed the PSO kinetic model [19][20][21]78 .…”
Section: Elovich Kinetic Model (Ekm)mentioning
confidence: 54%
“…The main extract species of inorganic substances from the Z. caduciflora series are Ca, K, and Mg because the primary biomass is growing in freshwater. The K concentration is 3.5–830 times higher than that of Ca and Mg in different biochar water lotions, which is a universal phenomenon in many researches (Alamin and Kaewsichan 2015). Among the three substances, there is an upward concentration trend on the whole, with the time gradually increasing to 1440 min.…”
Section: Resultsmentioning
confidence: 95%
“…A study by Alamin and Kaewsichan [70] has been carried out using two types of adsorbent mixtures, biochar calcium sulfate (BC) and biochar calcium sulfate hydroxyapatite (BCH), through pyrolysis. e study was conducted for the purpose of removing 2,4-dichlorophenol (DCP) from aqueous solutions.…”
Section: Biocharmentioning
confidence: 99%